Multidrug-Resistant Gram-Negative Bacteria: Inter- and Intradissemination Among Nursing Homes of Residents With Advanced Dementia. (29th April 2015) - D'Agata, Erika M. C.; Habtemariam, Daniel; Mitchell, Susan
<x content-type="archive" xml:space="preserve">Abstract</x> OBJECTIVE To quantify the extent of inter– and intra–nursing home transmission of multidrug-resistant gram-negative bacteria (MDRGN) among residents with advanced dementia and characterize MDRGN colonization among these residents. DESIGN Prospective cohort study. SETTING Twenty-two nursing homes in the greater Boston, Massachusetts, area. PATIENTS Residents with advanced dementia. METHODS Serial rectal surveillance cultures for MDRGN and resident characteristics were obtained every 3 months for 12 months or until death. Molecular typing of MDRGN isolates was performed by pulsed-field gel electrophoresis. RESULTS A total of 190 MDRGN isolates from 152 residents with advanced dementia were included in the analyses. Both intra– and inter–nursing home transmission were identified. Genetically related MDRGN strains, recovered from different residents, were detected in 18 (82%) of the 22 nursing homes. The percent of clonally related strains in these nursing homes ranged from 0% to 86% (average, 35%). More than 50% of strains were clonally related in 3 nursing homes. Co-colonization with more than 1 different MDRGN species occurred among 28 residents (18.4%). A total of 168 (88.4%), 20 (10.5%), and 2 (1.0%) of MDRGN isolates were resistant to 3, 4, and 5 different antimicrobials or antimicrobial classes, respectively. CONCLUSIONS MDRGN are spread both within and between nursing homes among residents with advanced dementia. Infection control interventions should begin to target this high-risk group of nursing home residents. Infect Control Hosp Epidemiol 2015;36(8):930–935